Determination of the Upper Limit Age of Jatropha Curcas Plantation for Optimum Yield Production - Tedla, Abeje; Minale, Mesafint; Eshetu, Reta (Asian Business Review, 2020)
Jatropha curcas (L.) provenances were grown to determine the upper limit age for maximum seed yield production.  The study had been conducted at Shewa robit district in the lowland areas of the North Shewa zone.  In this study, fourteen Jatropha curcas provenances had been collected from different parts of Ethiopia. Sixteen plants per plot had been planted in a randomized complete block design with three replications. The survival rate, number of branches, seed yields and growth parameter data had been collected from those plants. Survival rate ranged from 85-100%; root collar diameter was ranged between11.80 cm and 13.51 cm at the age of six years.  The maximum and minimum plant heights were 281.96 cm and 233.88 cm, respectively, at the age of five years after planting. Those different traits of Jatropha curcas indicated that statistically insignificant difference (p>0.05) except the seed yield of Cheffa provenance was significantly highest at the age of four years. The maximum seed yield (cheffa) was 38.837 ton/ha/year, and the minimum was 9.016 ton/ha/year (Jewuha) within the same year. All Jatropha curcas provenances seed yield was maximum at the age of four years and declined after six years of age.
Keywords: Growth parameter; Jatropha curcas; provenances; survival; yield